2020
DOI: 10.1007/s43465-020-00212-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Safety Knowledge and Practices: Is the Indian Orthopaedic Community Well-informed?

Abstract: Background In spite of frequent exposure to radiation, orthopaedic surgeons lack knowledge about radiation safety and do not comply with safety practices. We surveyed orthopaedic trainees and consultants in India to determine their knowledge and practices regarding radiation safety. Methods A questionnaire with 16 multiple choice questions was sent out using Google forms. We included practicing orthopaedic surgeons (consultants), fellows and trainees pursuing DNB, MS and D. Ortho courses across India. ResultsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This study is one of largest reported surveys undertaken to assess radiation safety knowledge and principles for orthopaedic surgeons. The findings are supported by other studies in the literature, [5][6][7][8][9][10][11][12][13][14][15][16][17] the majority of which were smaller local or regional surveys with less than 90 orthopaedic surgeon responses. [5][6][7][8][9][10][11] Overall, they showed limited radiation safety knowledge, lack of formalised training and poor usage of radiation protective equipment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study is one of largest reported surveys undertaken to assess radiation safety knowledge and principles for orthopaedic surgeons. The findings are supported by other studies in the literature, [5][6][7][8][9][10][11][12][13][14][15][16][17] the majority of which were smaller local or regional surveys with less than 90 orthopaedic surgeon responses. [5][6][7][8][9][10][11] Overall, they showed limited radiation safety knowledge, lack of formalised training and poor usage of radiation protective equipment.…”
Section: Discussionsupporting
confidence: 87%
“…Bowman et al 16 analysed 517 responses from US orthopaedic residents and reported substantial knowledge gaps in occupational safety and limited use of personal protective equipment with lack of availability of such equipment leading to decreased compliance. Ranade et al 17 reported the findings of their national survey of Indian orthopaedic trainees and consultants. Their results from 439 respondents showed limited radiation safety knowledge with only 16.2% being aware of the ALARA principle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some efforts, there has been a failure to recognize the increased occupational radiation exposure inherent with the increase in the frequency of fluoroscopically guided procedures (Chow et al 2013; Falavigna et al 2018; Harris et al 2019; Frane et al 2020; Ranade et al 2020). Furthermore, ignorance about safe radiation practice in the operating room includes using higher radiation C-arm default settings, absent or partial shielding (apron without thyroid shield, thyroid/waist without chest shield), and positioning in areas of maximum radiation scatter.…”
Section: Introductionmentioning
confidence: 99%